Characteristics of excesses of the perpetrator when committing a crime in complicityCharacteristics of excesses of the perpetrator when committing a crime in complicity - Tatyana SARY (Revista Naţională de Drept)
This article considers the characteristic of excesses of the perpetrator and the form of complicity in excesses of the perpetrator. The criminal-legal assessment of actions of accomplices in the conditions of excesses of the perpetrator of a crime is analyzed, when a number of problems are revealed, in particular: establishment of peculiarities of qualification depending on the type of excesses of the perpetrator of a crime; qualification of acts of co-perpetrators when they commit “outgrowing” crimes; qualification of crimes on the grounds of committing them by a group of persons by pre-planned conspiracy; qualification of acts of accomplices on the most serious qualifying feature of the crime, etc. Features of qualification of crimes in conditions of excesses of the perpetrator of a crime in the science of criminal law are traditionally considered in relation to quantitative and qualitative excesses